Virtue, valor and vanity: the founding fathers and the puruit of fame - Burns, Eric (New York : Arcade Publishing, 2007)
Biography.
Includes bibliographical references and index.
Keywords: United States -- Politics and government-1775-1783.3; Virtue-Political aspects-United States -- History,18th century